Maternal complications and neonatal outcomes in oligohydramnios - Rahman, Jahanara; Pervin, Shahana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Oligohydramnios is a condition of abnormally low amniotic fluid volume which is associated with adverse pregnancy outcomes. The objectives of the study were to find out the prevalence of oligohydramnios, to observe maternal complications associated with oligohydramnios, to detect neonatal morbidities and mortalities in oligohydramnios. Methods: A cross sectional, descriptive study was carried out in the in-patient department of obstetrics and gynaecology at Dhaka national medical college hospital between March 2016 and February 2017. Results: In this study 64 women had oligohydramnios among 1240 pregnant mothers admitted for delivery in obstetrics and gynaecology department and prevalence was 5.2%. Sixty six percent occurrence of oligohydramnios was due to premature rupture of membranes. The mean maternal age was 24.82±3.71 years. Maternal infections like, Respiratory tract infection (15%), vaginitis (20%), UTI (31%), hyperpyrexia (7%) and maternal systemic illness like, hypertension and diabetes mellitus were also noticed in 7% and 5% of the population. Majority (71%) of the mothers delivered by caesarian section and of them 31.82% was due to foetal distress. Unfavorable neonatal outcome was noticed as low birth weight (LBW) (28%), respiratory depression (32%), perinatal death (14%) and NICU admission (29%). Conclusions: No significant association was found between maternal systemic illness and oligohydramnios. Whereas maternal infection was found as a significant factor leading to PROM related oligohydramnios. Occurrence of caesarian sections and unfavourable neonatal outcomes were found high in oligohydramnios.